ANALISIS UJI VALIDITAS DAN PRAKTIKALITAS E-MODUL MOMENTUM DAN IMPULS BERBASIS MODEL PEMBELAJARAN DUAL SPACE INQUIRY - Zacka Hafidhon Faiz; Fuja Novitra; Hufri; Selma Riyasni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to analyze the validity and practicality of a momentum and impulse E-module based on the Dual Space Inquiry learning model as a digital teaching material in physics learning. The study employed a Research and Development (R&D) method using the 4D development model (Define, Design, Develop, Disseminate) and was limited to the Develop stage. Research instruments consisted of validation sheets and practicality questionnaires. The validity test involved experts in material, media, and instructional design, while practicality testing was conducted with teachers and students. Data were analyzed using descriptive quantitative analysis through validity and practicality index calculations. The findings showed that the average product validity score was 0.88, categorized as valid, while the overall E-module validation score reached 0.93, also categorized as valid. The practicality test results indicated average scores of 0.90 from students and 0.91 from teachers, both categorized as very practical. Therefore, the momentum and impulse E-module based on the Dual Space Inquiry learning model is considered feasible and demonstrates a high level of usability for implementation in physics learning.